Human impacts on sub-Antarctic terrestrial environments - Bergstrom, DM; Selkirk, PM (Papers and Proceedings of the Royal Society of Tasmania, 2007)
Sub-Antarctic islands are some of the rarest ecosystems on the planet and therefore are highly significant. Around 200 years of human activities have left a legacy of substantial impacts. We explore these under the collective headings of resource harvesting, local impacts and habitat loss, homogenisation of biota and human-influenced climate change. Past human activities such as sealing and whaling have left seal species still in recovery phases, and infrastructure that continues to break down and pollute the local environment. Modern-day scientific stations have variously-sized footprints of buildings and tracks, and legacies of contaminants, particularly oils spills. On some islands, alien species have established and there is a range of impacts associated with such taxa ranging from transient to extensive, permanent transformation of ecosystems. Such impacts are being confounded by human-induced climate change. By projection, it is expected that both direct and indirect human impact will continue into the future. It is appropriate to plan all future human activity in ways that will minimise further burden on these ecosystems.